2023
DOI: 10.3390/taxonomy3020013
|View full text |Cite
|
Sign up to set email alerts
|

A New Species of Pareas Wagler, 1830 (Squamata, Pareidae) from Northwestern Yunnan, China

Abstract: A new species of Pareas Wagler, 1830 is described from Dulongjiang Township, Gongshan County, Yunnan Province, China. Phylogenetically, the new species is most closely related to Pareas kaduri Bhosale, Phansalkar, Sawant, Gowande, Patel and Mirza, 2020; however, the genetic divergence (uncorrected p-distance) of the cyt b gene between the new species and P. kaduri reached 9.4%. Morphologically, the new species can be distinguished from P. kaduri by the absence of preoculars, loreal bordering the orbit, the fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Pareas baiseensis sp. nov. differs from Pareas tigerinus by the dorsal surface of the head, which is light brown with dark brown spots (vs. dorsal surface of head solid black or reddish-brown); two anterior temporals (vs. one anterior temporal); two or three suboculars (vs. suboculars fused with postoculars); a higher number of ventrals (187–191 vs. 160–171); and a higher number of subcaudals (89–97 vs. 62–64) [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Pareas baiseensis sp. nov. differs from Pareas tigerinus by the dorsal surface of the head, which is light brown with dark brown spots (vs. dorsal surface of head solid black or reddish-brown); two anterior temporals (vs. one anterior temporal); two or three suboculars (vs. suboculars fused with postoculars); a higher number of ventrals (187–191 vs. 160–171); and a higher number of subcaudals (89–97 vs. 62–64) [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…The description of Pareas baiseensis sp. nov. from southern China brings the total number of recognized Pareas species to 30, of which 24 occur in China [2,4,14,15]. The genus Pareas has an ancient origin and poor migration ability, and the morphological difference between different species are subtle [9,21,[40][41][42]; a large range of intensive sampling is helpful in discovering cryptic species, especially for some widely distributed types with unclear internal relationships, so sampling should be increased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All new sequences have been deposited in Gen-Bank. Aplopeltura boa (Boie, 1828) was selected as the outgroup according to Liu et al [23]. Details of all the sequences used in this study can be found in Table 1.…”
Section: Molecular Analysesmentioning
confidence: 99%